2008
DOI: 10.1136/jech.2006.052993
|View full text |Cite
|
Sign up to set email alerts
|

Social capital and self-rated health in urban low income neighbourhoods in Chile

Abstract: Neighbourhood social cohesion, measured by trust and reciprocity, is associated with higher self-rated health. However, social participation did not appear to be associated with better health in this predominantly low income neighbourhood. These findings provide preliminary support to the relevance for social capital as a determinant of health in Chile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
2
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 16 publications
0
21
2
1
Order By: Relevance
“…The gini coefficient, a measure of income inequality, has had a more inconsistent relationship with suicide. Higher inequality sometimes correlated with higher rates of suicide (Sapag et al, 2008), sometimes correlated with lower rates of suicide (Lester, 1996), and sometimes had no correlation at all (Andr es, 2005).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The gini coefficient, a measure of income inequality, has had a more inconsistent relationship with suicide. Higher inequality sometimes correlated with higher rates of suicide (Sapag et al, 2008), sometimes correlated with lower rates of suicide (Lester, 1996), and sometimes had no correlation at all (Andr es, 2005).…”
Section: Introductionmentioning
confidence: 96%
“…Social capital has been shown to positively impact general health outcomes, such as mortality (Kawachi et al, 1997), as well as self-rated perceptions of health (Borges et al, 2010;Hurtado et al, 2011;Sapag et al, 2008). Social capital has also been shown to influence specific health outcomes such as oral health (Furuta et al, 2012) and obesity (Kim et al, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…41 In Chile, a recent study of social capital and self-rated health in urban low-income neighborhoods identified five domains of social capital: perceived trust in neighbors, perceived trust in organizations, reciprocity within the neighborhood, neighborhood integration, and social participation. 42 Trust, reciprocity, and social cohesion were associated with better self-rated health. In Sweden, collective social capital, particularly trust and social participation, was positively related to better self-rated health.…”
Section: Social Capital and Social Networkmentioning
confidence: 99%
“…While there is indeed a substantial literature on the health benefits of social capital, the bulk of the previous research has dealt primarily with developed nations (Habibov & Afandi, 2011;Kumar et al, 2012;Mansyur, Amick, Harrist & Franzini, 2008;Sapag, Aracena, Villarroel, Poblete, Berrocal, Hoyos, Martinez & Kawachi, 2008;Yip et al, 2007). In a recent article based on the large Gallop World Poll dataset covering 139 countries, Kumar et al (2012) observe that the reputed link between "social capital and health in non-Western countries is a yet a matter of debate" (pp.…”
Section: Empirical Gapmentioning
confidence: 99%
“…This study also extends the existing literature by turning the analytical focus on a group of Asian countries, which has not received a great deal of scholarly attention. Some researchers in a limited number of studies have explored the association between social capital and health in various parts of developing and transitional societies including, for example, rural China (Yip et al, 2007), a low income community in Chile (Sapag et al, 2008), Hungary (Skrabski, Kopp & Kawachi, 2004), Russia (Ferlander & Makinen, 2009;Rojas & Carlson, 2006), the Middle East (Baron-Epel et al, 2008), the Commonwealth of Independent States (d 'Hombres et al, 2010), and the South Caucasus region (Habibov & Afandi, 2011). Based on the analysis of the Asian Barometer Survey, the current research adds to these and other related studies in testing the validity of the social capital argument outside the context of economically more developed Western liberal democracies.…”
Section: Summary Of Findingsmentioning
confidence: 99%